Polish Code of Professional Ethics in Accounting – A Survey Among Accountants and Other Professionals. - Marek CIESLAK (Communications of International Proceedings, 2020)
The need for a code of ethics to ensure equality for stakeholder groups is taken for granted. The Code of Professional Ethics in Accounting regulates the ethical behavior of people professionally involved in accounting. The conducted survey allowed for the formulation of a number of conclusions regarding the Code. Although the respondents considered the principles to be correct, they were less willing to support solutions binding the practice of the accounting profession with compliance with the principles contained in the Code. The largest number of respondents decided that the requirement for practicing the profession in accounting should be observance of the principle of professional secrecy, and the least that it should be compliance with the rules of conduct in the event of a conflict of interest.
Keywords: Accounting ethics; accountants; code of ethics; Poland.